Comparative genomics and phylogenetic analysis of complete chloroplast genome of Scaphium scaphigerum (WALL. EX G. DON) G. PLANCH (Dhaka University Journal of Biological Sciences, 2025)
Scaphium scaphigerum (Wall. ex G. Don) G. Planch. is a threatened medicinal tree of Bangladesh, belonging to the family Malvaceae. This study unveiled the first chloroplast genome of the species, spanning 160,927 bp with a GC content of 36.89%. The plastome exhibited the typical orbicular quadripartite structure of angiosperms, consisting of a pair of inverted repeat regions (25502 bp), isolated by a large-single copy region (90012 bp) and a small single-copy region (19911 bp). The plastome harbored 128 genes in total, including 85 protein-coding genes, 35 tRNAs and 8 rRNAs. Comparative analyses with several other species revealed high synteny and lack of major rearrangements, along with similar gene order and GC content. The plastome contained 115 SSRs, predominantly comprising mononucleotides (78). Among the longer repeats, palindromic sequences were the most frequent (22). Nucleotide diversity analysis identified two hypervariable sites (ycf1 and ndhI) in the small single-copy region, which will facilitate DNA barcoding endeavors. Phylogenetic analysis showed close alliance of S. scaphigerum within Sterculioideae, with strong bootstrap support. Molecular dating suggested that the species originated during the Lutetian age (48.23 MYA) of the Cenozoic era.Dhaka Univ. J. Biol. Sci. 34(1): 119-143, 2025 (January)